The Influence of Trust, Service Quality and Brand Image on Customer Decisions: A Case Study of Prudential in Babura Sunggal Village - Hutagaol, Reski Br; Alfifto, Alfifto; Tarigan, Eka Dewi Setia (Journal of Management and Business Innovations, 2025)
This study aims to understand and analyze the impact of trust, service quality, and brand image on Prudential customer decisions in Babura Sunggal Village. Applying quantitative methods, the researcher selected 99 respondents from a total of 11,330 residents using purposive sampling techniques, then analyzed the data through multiple linear regression. The results of the study show that the three variables have a significant influence on customer decisions. Trust shows the greatest influence with a significance value of 0.000, which indicates a very strong relationship. Service quality has a significant influence with a significance value of 0.035. Meanwhile, brand image shows an important influence with a significance value of 0.026 and a calculated t value of 2.266, which exceeds the t table of 1.985. Together, trust, service quality, and brand image are proven to have a significant impact on customer choice. This can be seen from the calculated F value which is higher than the critical F and the significance level of 0.000. This finding confirms that these three factors are strategic elements that are crucial for insurance companies in designing marketing strategies, attracting new customers, and improving customer satisfaction. Keywords : Brand Image, Customer Decision, Service Quality, Trust